Homochirality in biomineral suprastructures induced by assembly of single-enantiomer amino acids from a nonracemic mixture - Jiang, W.; Athanasiadou, D.; Zhang, S.; Demichelis, Raffaella; Koziara, Katarzyna; Raiteri, Paolo; Nelea, V.; Mi, W.; Ma, J.A.; Gale, Julian; McKee, M.D. (NATURE PUBLISHING GROUP, 2019)
© 2019, The Author(s). Since Pasteur first successfully separated right-handed and left-handed tartrate crystals in 1848, the understanding of how homochirality is achieved from enantiomeric mixtures has long been incomplete. Here, we report on a chirality dominance effect where organized, three-dimensional homochiral suprastructures of the biomineral calcium carbonate (vaterite) can be induced from a mixed nonracemic amino acid system. Right-handed (counterclockwise) homochiral vaterite helicoids are induced when the amino acid l-Asp is in the majority, whereas left-handed (clockwise) homochiral morphology is induced when d-Asp is in the majority. Unexpectedly, the Asp that incorporates into the homochiral vaterite helicoids maintains the same enantiomer ratio as that of the initial growth solution, thus showing chirality transfer without chirality amplification. Changes in the degree of chirality of the vaterite helicoids are postulated to result from the extent of majority enantiomer assembly on the mineral surface. These mechanistic insights potentially have major implications for high-level advanced materials synthesis.